Recommendations for vaccination in multiple myeloma: a consensus of the European Myeloma Network - Ludwig, Heinz (Leukemia, 2020)
Vaccination is one of the most successful medical interventions that has saved the life of millions of people. Vaccination is particularly important in patients with multiple myeloma, who have an increased risk of infections due to the disease-inherent immune suppression, and because of the immune suppressive effects of therapy. Hence, all appropriate measures should be exploited, to elicit an effective immune response to common pathogens like influenza, pneumococci, varicella zoster virus, and to those bacteria and viruses (haemophilus influenzae, meningococci, and hepatitis) that frequently may pose a significant risk to patients with multiple myeloma. Patients after autologous, and specifically after allogeneic transplantation have severely reduced antibody titers, and therefore require a broader spectrum of vaccinations. Response to vaccination in myeloma often is less vigorous than in the general population, mandating either measurement of the postvaccination antibody titers and/or repeating the vaccination. Here, we compile the existing data on vaccination in multiple myeloma and provide recommendations for clinical practice.